2020
DOI: 10.1039/d0an00703j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic molecularly imprinted conducting polymer for determination of praziquantel enantiomers in milk

Abstract: A new selective adsorbent based on magnetic molecularly imprinted conducting polymer was firstly synthetized and applied to the magnetic solid phase extraction (MSPE) for the determination of PZQ enantiomers in milk samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the adsorption and quantitative analysis of biomarkers, many other materials can be modified on Fe 3 O 4 microspheres. For example, poly(glycidyl methacrylate), 61 2-anilinoethanol, 62 porous TiO 2 , 63 chitosan, 64 carbon quantum dots, 65 ionic liquids, 66 reduced graphene oxide (rGO), 67 metal–organic frameworks (MOF), 68 pyrrole, 69 dopamine 65 and other substances can enhance the performance of magnetic materials and assist the imprinting process. Of course, Fe 3 O 4 microspheres can also be directly bonded with functional groups.…”
Section: Preparation and Surface Modification Of Mmipsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the adsorption and quantitative analysis of biomarkers, many other materials can be modified on Fe 3 O 4 microspheres. For example, poly(glycidyl methacrylate), 61 2-anilinoethanol, 62 porous TiO 2 , 63 chitosan, 64 carbon quantum dots, 65 ionic liquids, 66 reduced graphene oxide (rGO), 67 metal–organic frameworks (MOF), 68 pyrrole, 69 dopamine 65 and other substances can enhance the performance of magnetic materials and assist the imprinting process. Of course, Fe 3 O 4 microspheres can also be directly bonded with functional groups.…”
Section: Preparation and Surface Modification Of Mmipsmentioning
confidence: 99%
“…Among them, functional monomers, which affect ligand receptor interactions and determine the affinity and selectivity of MIPs, are indispensable components in the preparation of MIPs. Despite the trend of gradual simplification of the current MIPs imprinting methods, some natural functional monomers such as pyrrole, 69 dopamine, 65 and norepinephrine 149 have been applied, but there are many alternative kinds of functional monomers. Before imprinting, multiple preselection experiments need to be carried out to obtain the functional monomer most suitable for the template molecule.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…On the basis of the negative values of ΔG and ΔH, this results in the complexation of the monomer with praziquantel in aqueous solution spontaneously forming stable complexes. Moreover, the results of molecular geometric conformation simulation showed that four hydrogen bonds and one π–π stacking interaction are established between praziquantel and pyrrole, which explains the formation of praziquantel and pyrrole prepolymer complex at the molecular level [ 125 ]. Through PM3 and DFT theoretical simulation methods, the Muliken charge on each atom of the fluazuron optimized geometric structure can be obtained, which can quantitatively reveal the existence of six regions with a high electron charge density.…”
Section: Computational Simulation and Mip Identification Mechanismmentioning
confidence: 99%
“…The validated PT-MIP-SPE proved to be economical, simple, easy-to-perform, and potentially applicable for the extraction of MALs in complicated samples. Nascimento et al (2020) firstly synthesized a new selective adsorbent based on magnetic molecularly imprinted polypyrroleconducting polymer (MMIPPy) and applied it to the MSPE of praziquantel (PZQ) enantiomers [(R)-(−)-PZQ and (S)-(+)-PZQ] combined with HPLC-DAD determination. Under optimal conditions, excellent linearity was attained in a range of 0.01-10 µg/ml, with correlation coefficients higher than 0.98 and RSDs less than 15%.…”
Section: Other Antibioticsmentioning
confidence: 99%